HUBUNGAN PENERAPAN SMK3 DENGAN ANGKA KEJADIAN KECELAKAAN KERJA DI PT PUPUK ISKANDAR MUDA TAHUN 2025 - Tampubolon, Elmina (Jurnal Inovasi Kesehatan Masyarakat, 2025)
Occupational Safety and Health (K3) is a crucial aspect in the world of work to protect workers from the risk of accidents and occupational diseases. The development of the industrial world, the world of work is always faced with new challenges. Various new challenges emerge along with the development of the era. However, this development is always accompanied by new problems, one of which is work accidents. The Occupational Safety and Health Management System (SMK3) regulated in PP No. 50 of 2012 is designed to increase the effectiveness of K3 protection in a planned and measurable manner. However, the implementation of SMK3 in various industrial sectors still faces various obstacles. This study aims to Analyze the Relationship between the Implementation of SMK3 and the Number of Occupational Accidents at PT Pupuk Iskandar Muda in 2025. This study uses a quantitative descriptive research method. The study population is all employees at PT Pupuk Iskandar Muda. The total population of PT Pupuk Iskandar Muda workers as of January 2025 was 547 with a sample size of 85 people. Data were analyzed using the chi-square test and logistic regression. Based on the results of the study, there is a relationship between Policy (P-Value 0.007), Planning (P-Value 0.005), Plan Implementation (P-Value 0.007), Performance Monitoring and eval_uation (P-Value 0.02), Performance Review and Improvement (P-Value 0.04) with the number of work accidents. Based on the results of the multivariate analysis, it was found that the most dominant factor related to the Number of Work Accidents is Plan Implementation with a p-value of 0.01 where the Exp (B) value is 3.6. It is hoped that the Management of PT Pupuk Iskandar Muda can strengthen the implementation of the K3 plan that has been prepared by ensuring that all K3 work programs are carried out according to schedule, not just stated in formal documents.